The Use of Indonesian by Danish Athlete "Mathias Christiansen" in Various Competitions as a Form of Love for the Indonesian Language - Aqilla Dwi Ranaa; Fathiyya Adzkiaunnisa; Serie Korina Sekar Kinanti; Satrio Kusuma Ardi; Afiq Razaki Saputra (KIRANA : Social Science Journal, 2026)
This research analyzes the use of Indonesian by an athlete from Denmark, Mathias Christiansen, in various competitions as a form of love for the Indonesian language and culture. The method used is qualitative analysis of interactions and interviews conducted by Christiansen during competitions in Indonesia and internationally. The results of the research show that Christiansen not only communicates well in Indonesian but also expresses a deep appreciation and interest in Indonesian culture and language. The use of this language is a means of building closeness with fans and the Indonesian people, as well as demonstrating the positive impact of good mastery of Indonesian by foreigners, thereby increasing Indonesia's international recognition. It is hoped that these findings will provide insight into the role of language as a bridge between cultures in the world of sport.